Menimbang Kembali Kebijakan Sistem Zonasi Dalam Penerimaan Peserta Didik Baru di Bandar Lampung - Kartika Marini; Bambang Utoyo (Jurnal Administrativa, 2019)
The emergence of superior schools and suburban schools in Indonesia is caused by the selection of the quality of prospective students in New Student Admissions. One of the government's efforts to improve and equalize quality education is implementing a zoning system at New Student Admissions. Through the zoning system, students who live close to the school are more likely to be accepted into the education unit. The zoning system policy has been regulated in Permendikbud Number 14 of 2018.This study aims to analyze the implementation and the obstacles encountered in the Admission Policy for New Student Zoning Systems in Bandar Lampung City Public High School, especially SMAN 9 Bandar Lampung and SMAN 14 Bandar Lampung. The type of this research is descriptive with a qualitative approach.The techniques of data collections used interviews, documentation and observation.Based on the results of this study showed that the implementation of the zoning system in PPDB SMA in Bandar Lampung City, especially SMAN 9 Bandar Lampung and SMAN 14 Bandar Lampung had gone quite well.This can be seen from the research results of researchers who are associated with 6 variables belonging to Van Meter and Van Horn, including variable size and policy objectives, resource variables, characteristics of executing agents, attitudinal / disposition variables, communication variables between implementing agents and economic, social and political environment variables.However, there were several obstacles in implementation namely the application provided is disrupted, the network is inadequate, the quota outside the zoning system affects the non-fulfillment of capacity at Bandar Lampung Public High School, and the community's mindset of the quality of superior schools has not changed.